Artificial Induction of Polyploidy in Blueberry Breeding: A Review - Ye Chu; Paul M. Lyrene (HortScience)
Blueberry planted acreage has increased rapidly during the past four decades, and blueberry consumption has kept pace. The environments across blueberry growing regions are highly heterogeneous. Variable factors include weather, soils, cultivation practices, biotic stress, and abiotic stress. Broadening the genetic diversity of the blueberry breeding gene pool will enable the development of blueberry cultivars adapted to specific growing regions. The primary gene pool for blueberry breeders includes cultivated tetraploids and hexaploids. The tetraploids include cultivars and advanced selections of northern highbush, southern highbush, lowbush, and half highbush; the hexaploids are the rabbiteye cultivars. The secondary gene pool encompasses diploid, tetraploid, and hexaploid wild blueberries in Vaccinium section Cyanococcus. The tertiary gene pool consists of 300 to 400 Vaccinium species in sections other than Cyanococcus. These are native to many parts of the world. Blueberry breeding began with interspecific hybrids in section Cyanococcus. Subsequent breeding has used diploid, tetraploid, and hexaploid Cyanococcus species with limited use of species from other Vaccinium sections. A strong triploid block and partial to total sterility in progeny from heteroploid crosses have limited the use of some species in breeding. Unreduced gametes allow the production of tetraploid hybrids from diploid × tetraploid crosses and hexaploid hybrids from triploid × hexaploid and triploid × triploid crosses. Production of polyploids by in vitro and in vivo treatments with antimitotic agents can expedite interspecific and intersectional hybridization. This review addresses the contribution of artificial induction of polyploidy to blueberry genetic improvement and discusses additional possible applications of artificial induction of polyploidy for blueberry breeding.